Marija Milutinović Punktatorka, Teacher: The First Woman Lawyer in Serbia - Vasojević, Nena A.; Knežević Lukić, Nevenka D. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The paper shows the development of legal representation in the Principality of Serbia, with a special focus on the professional participation of women in court proceedings, shown through the character and work of Marija Milutinović Punktatorka, a teacher and the first female attorney in Serbia. In the judicial system of the Principality of Serbia, women were not prohibited from practicing law, which enabled an educated woman to pave the way for future women lawyers in the period of ‘Little Serbia’. In the relevant literature, one can find rare texts in which the life and work of Marija Milutinović are mentioned casually and inconspicuously without an стр. 00–000 24 insight into the complete biography. By researching unpublished archival sources, significant information was obtained about the life and work of Marija Milutinović Punktatorka, the wife of the poet Sima Milutinović Sarajlija and the mother of the architect and professor of the Grande école, Dragutin (Dragiša) Milutinović. Marija Milutinović Punktatorka was born in 1809 into the Popović family in Timisoara. As the ‘first Serbian’ teacher, she educated girls and thus strove for women in the 19th century to fight for their place in the society. She was educated in Buda, where she also studied several sciences privately, with a ‘very good approach and accuracy’. After the death of her husband, in October 1848, she opened a private elementary school in Belgrade. Soon, in 1849, she entered the civil service and started working as a teacher at the state school in Belgrade near the Great Church (Saborna crkva), where she received a pension in August 1874. Marija Milutinović’s main motive to engage in legal representation stemmed from humane motives and not from material benefit. She practiced law even during her married life. She charged wealthier people, whom she successfully represented and won lawsuits in court with large compensation—modest, symbolic sums, more as a reward than as a fee (Игњатовић, 1860, p. 24). Even after her husband’s death (1847), she continued to practice law and fulfil her husband’s bequest, providing legal aid and representing the poor free of charge, which reflected badly on her impoverished family fund (Јавор, 1862–1863; 1874–1893, p. 350). During the working life of Marija Milutinović, legal regulations did not prohibit women from practicing law, nor did the prohibition result indirectly. With the entry into force of the Law on Legal Representatives (1862), the previous decrees and orders, which often ad hoc solved the issue of providing legal aid in the Principality of Serbia. Officially, Marija Milutinović did not submit a request to be recognized as a lawyer before the competent authorities because she did not graduate from the Faculty of Law. In a formal sense, Marija Milutinović was never recognized by the Мinistry as having the right to call herself a lawyer. Based on the real facts, it cannot be disputed that Marija Milutinović Punktatorka was the first woman in the Principality of Serbia to engage in a free profession, in this particular case, legal work.
Keywords: women; first woman lawyer; legal representation; Marija Milutinović Punktatorka; education